Resources Mobilization for Excellence Academic in School - Khiawwan, Kanchana; Wanngoen, Chatchadaporn; Tamprayort, Wanwipa (Journal of Humanities and Social Sciences Nakhon Pathom Rajabhat University, 2023)
Resource mobilization for academic excellence of educational institutions is an academic article that wants to present a quality management process. “Par ADVICE” is a featured in the management of participatory and Kanyanamit management.The management of educational institutions, the mobilization of resources aimed at academic excellence of educational institutions. The management process consists of two key principles: participation, 1.1) decision making, 1.2) implementation & responsibility, 1.3) evaluation & development, 1.4) benefit join to outcome and 2) managing the Kalyanamit (ADVICE) 5 steps. This starts from 2.1) Analysis of the organization and quality goals using SWOT analysis and 4M’S 2.2) Designing a quality management plan using 3P principles in operation 2.3) Driving vision into action 2.4) Practice and continuous learning in accordance with the quality culture. 2.5) Evaluation of management must understand the context of the educational institution Analyze the strengths, weaknesses, opportunities and goals of the school. The “Par ADVICE” quality management process is one of the processes that can drive educational institutions towards academic excellence in education management.